2019
DOI: 10.1111/acps.13017
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed cardiovascular disease prior to cardiovascular death in individuals with severe mental illness

Abstract: Objective To examine whether individuals with schizophrenia ( SCZ ) or bipolar disorder ( BD ) had equal likelihood of not being diagnosed with cardiovascular disease ( CVD ) prior to cardiovascular death, compared to individuals without SCZ or BD . Methods Multivariate logistic regression analysis including nationwide data of 72 451 car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 82 publications
1
27
1
1
Order By: Relevance
“…This is contrary to most earlier research which found elevated mortality risk in both sexes (Ösby et al ., 2001 ; Crump et al ., 2013 ; Westman et al ., 2013 ; Pan et al ., 2020 ), although some revealed slightly higher cardiovascular mortality in women than in men (Ösby et al ., 2001 ; Crump et al ., 2013 ). A recent study further demonstrated that female patients with bipolar disorder were more likely to die of undiagnosed cardiovascular diseases than male counterparts (Heiberg et al ., 2019 ). Lifestyle modification, early detection and optimal treatment of comorbid diabetes, dyslipidaemia and hypertension should be implemented to reduce cardiovascular mortality in bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to most earlier research which found elevated mortality risk in both sexes (Ösby et al ., 2001 ; Crump et al ., 2013 ; Westman et al ., 2013 ; Pan et al ., 2020 ), although some revealed slightly higher cardiovascular mortality in women than in men (Ösby et al ., 2001 ; Crump et al ., 2013 ). A recent study further demonstrated that female patients with bipolar disorder were more likely to die of undiagnosed cardiovascular diseases than male counterparts (Heiberg et al ., 2019 ). Lifestyle modification, early detection and optimal treatment of comorbid diabetes, dyslipidaemia and hypertension should be implemented to reduce cardiovascular mortality in bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the general population, the risk of cardiovascular mortality is almost 2-fold in bipolar disorder and 2 to 3-fold in schizophrenia ( 3 5 ). Undiagnosed CVD prior to cardiovascular death is more common in psychotic disorders than in the general population ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that patients with schizophrenia are more likely to receive suboptimal medical care for their physical illnesses, which has resulted in excessive mortality. [29][30][31][32][33][34] Such suboptimal medical care is due to complex reasons, possibly related to patients' decreased ability for self-care and limited access to medical service. 35,36 Evidence has suggested that the association between risk of sudden cardiac death and residence in a rural area is related to the referral rate of specialist care.…”
Section: Discussionmentioning
confidence: 99%